Lap number properties for p-Laplacian problems investigated by Lyapunov methods - Gentile, Claudia B.; Bruschi, Simone M. (Elsevier B.V., 2007)
In this work we consider a one-dimensional quasilinear parabolic equation and we prove that the lap number of any solution cannot increase through orbits as the time passes if the initial data is a continuous function. We deal with the lap number functional as a Lyapunov function, and apply lap number properties to reach an understanding on the asymptotic behavior of a particular problem. (c) 2006 Published by Elsevier Ltd.
Keywords: p-Laplacian; reaction-diffusion; lap number; omega-limit